2023
DOI: 10.1128/spectrum.01956-22
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Correlations of the Oral and Gut Fungal Microbiome with Hypertension

Abstract: Our study fills the gap in human studies investigating the oral and gut fungal microbiota in association with blood pressure. It characterizes the diversity and composition of the oral and gut fungal microbiome in human subjects, elucidates the dysbiosis of fungal ecology in a hypertensive population, and establishes oral-gut fungal correlations and fungus-clinical parameter correlations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…Fungi derived from dietary sources, such as mushrooms and Ganoderma, were specifically excluded as these fungi are typically transient and lack activity in the gut. Utilizing this database, we observed that Saccharomyces was the most prevalent genus in this cohort, which is supported by previous findings [ 27 29 ]. Especially, S. cerevisiae accounted for 41.5% of the fungal composition.…”
Section: Discussionsupporting
confidence: 91%
“…Fungi derived from dietary sources, such as mushrooms and Ganoderma, were specifically excluded as these fungi are typically transient and lack activity in the gut. Utilizing this database, we observed that Saccharomyces was the most prevalent genus in this cohort, which is supported by previous findings [ 27 29 ]. Especially, S. cerevisiae accounted for 41.5% of the fungal composition.…”
Section: Discussionsupporting
confidence: 91%
“…While bacteria are the primary components of the gut microbiome, other symbionts like viruses, fungi, and archaea also play significant roles. Recent studies ( Chen et al, 2023 ; Li et al, 2024 ) have suggested a link between viruses and the incidence of atherosclerotic diseases, indicating that other components of the human symbiotic microbial system, beyond bacteria, may have associations with PAD that warrant further investigation. Our current analysis focuses solely on the correlation between the gut microbiota and PAD, leaving the relationships between other components of the human symbiotic microbial system and PAD to be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiome diversity decrease emblematizes that pathogenic strains occupy the ecological niche of the intestinal mucosa, causing harmful bacterial metabolites or gut bacteria to enter the blood through the disrupted intestinal barrier and promote systematic chronic subacute in ammation [22,23]. This ongoing systemic in ammation can drive the progression of metabolic disease [24], cardiovascular disease [25],…”
Section: Discussionmentioning
confidence: 99%